Karakteristik Tepung Ampas Tahu yang Difermentasi dengan Lactobacillus plantarum terhadap kandungan Daidzein, Glycitein, dan Genistein - Eka Fitasari; Budi Santosa (Universitas Tribhuwana Tunggadewi, 2020)
Animal feed should ideally be inexpensive and not competing with humans. Ampas know is a waste of the manufacture of tofu that contains protein and high energy. Its use has problems due to the existence of antinutrient and cannot be kept long. Lactobacillus Plantarum is a lactic acid (Gram-positive) bacteria used in the fermentation process to improve the quality of feed. The goal of fermentation is to remove the anti-nutrients that exist in the tofu pulp and increase the content of Isoflavone (Daidzin, Glycitein, and Genistein) and Isoflavone is a source of antioxidants important to growth. The study uses a Completely Randomized Design with 5 treatment of microbial culture concentrations of 1%, 5%, 10%, 15%, and 20% (V/w), respectively repeated 3 times. The result of analyzes in the pulp of tofu fermentation suggests that fermentation by Lactobacillus Plantarum can increase the content of Daidzein, Glycitein, and genistein with the highest value resulting from the use of L. Plantarum 20% respectively 191.21 + 24.9 μg/g, 85.96 μg/g, and 120.82 μg/g. It can be concluded that the higher the use of the concentration of L. Plantarum in tofu pulp can increase the levels of isoflavone, so it is advisable to conduct research with the concentration of L. Plantarum higher in tofu pulp